Uncovering men's stereotype content (warmth and competence) associated with a representative range of male body size categories. (June 2021) - Baker, Amanda; Florack, Arnd
Highlights: Men's warmth and competence perceptions are increasingly severe with adiposity. Normal weight men are favored compared to underweight men, revealing further stigma. Empathy helps reduce bias toward disadvantaged BMI classes on perceptions of warmth. Empathic concern for stigmatized groups does not facilitate perceptions of competence. Protestant ethics amplifies judgements of warmth across all male BMI categories. Abstract: Research indicates that 40 % of men experience weight-related stigmatization. Yet perceptions of body size continue to be understudied in men and the stereotype content of men's weight status remains largely unknown. Grounded in Stereotype Content Model, the research aims to uncover men's stereotype content associated with distinct body sizes. A pilot study tested the methodological design using a representative measure of BMI-specific images among a sample of undergraduate men ( N = 80). Study 1 included the BMI-specific images to assess stereotype content among a broad online sample ( N = 142) and explored how participant BMI relates to such perceptions. Study 2 included images of real men to increase the ecological validity of our findings ( N = 152). We also included empathy and protestant ethics to examine possible interaction effects. Results revealed that normal to overweight men scored highest on warmth and competence, while underweight and obese classes were perceived less favorably and, evidently, stereotype perceptions were increasingly severe with adiposity. Empathy moderated evaluations of warmth toward stigmatized groups, and protestant ethics moderated warmth appraisals for underweight and normal weight targets but did not influence perceptions of competence. Overall, weight stereotype content should be considered when understanding stigma-related experiences in men.